“Whether or not there will be a Great Russia, but one must be orthodox in any case”: the question of “Russia — Europe” dichotomy in the historiosophic views of G. V. Florovsky of the “Eurasian” period of his work - Alexander Dubonosov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article is an attempt to show the development of historiosophic views of G.V. Florovsky during "Eurasian" period of his creativity on the example of his critique of the idea of "cultural-historical morphology" by N.S. Trubetskoy. The Eurasian movement, whose participants and founders were Florovsky and Trubetskoy, was characterized at an early stage of its development by a considerable ideological and ideological pluralism of its participants. It is noted that Florovsky's historiosophic views began to take shape even before he joined the Eurasian movement. As a result of the revision of the established historiosophy of Russian thought, Florovskij comes to criticize the concept of N.J. Danilevskij, to the continuers of whose ideas Florovskij included N.S. Trubetskij. Despite his disagreement with Troubetzky's ideas, which later became the basis for the "scientific" stage of Eurasianism, Florovskij takes part in the first collections "Exodus to the East" and "On the Roads. The correspondence between Florovsky and Trubetskoy shows that Florovsky's gradual development of historiosophic views and his shift of interest from the problem of nationality (from the dichotomy "Russia-Europe") to the problem of building religious culture leads him to a gradual departure from Eurasianism.